After 12. Issue 3 (27th January 2016) - Ghosh Dastidar, Surajit; Jain, Nitin Kumar
Abstract : Title: – After 12. Subject area: – Entrepreneurship. Study level/applicability: – The case is suitable for analysis in an undergraduate/graduate entry level course on entrepreneurship. It may also be taught in a course for non-business majors who are unfamiliar with basic business concepts. Case overview: – Shrey Gupta and Manoj Agarwal were the co-owners of "After 12", a food facility in the Dhanakwadi area of Pune, India. In only nine months, their food enterprise had become quite popular among the local college going crowd. They were doing brisk business and sales had picked up quite a bit in the last two months. They both were quite pleased with the progress of their business. However, in spite of increasing sales figures in the last few months they hardly generated any profits. The revenue they generated was completely spent on buying raw materials like vegetables and other food materials and the rest was used in the payment of utility bills and wages of the cook and the helper. They only had enough money to continue for another month or so. Both pondered about what is the way to proceed. What can be done to make it sustainable? How would they arrange the extra money to get them going? Should they close down "After 12"? Expected learning outcomes: – The case will aid students to understand: how small businesses are started and may fail; the importance of researching your business idea; and SWOT analysis. Supplementary materials: – Teaching notes are available for educators only. Please contact your library to gain login details or emailsupport@emeraldinsight.com to request teaching notes.